Serological Evidence of Potential Marburg Virus Circulation in Livestock and Dogs in Ghana - Theophilus Odoom; Sherry Ama Mawuko Johnson; William Tasiame; Meyir Y. Ziekah; Joseph K. Abuh; Benita Anderson; Fenteng Danso; Richard K. Abbiw; Franklin Y. Nuokpem; Emmanuel Allegye-Cudjoe; Charles Lewis; Bonto Faburay (Pathogens)
Marburg virus disease (MVD) is a zoonotic hemorrhagic disease with an estimated case fatality rate of up to 88%. Ghana recorded its first human MVD outbreak in June 2022 and although the outbreak was quickly brought under control, the transmission dynamics of the disease remained unclear. We assessed the presence of Marburg virus (MARV) antibodies in livestock and dogs and identified associated risk factors that increased the risk of these animals being exposed to MARV in five regions of Ghana. Sera collected from 3113 livestock and dogs in 2 climatic seasons (rainy and dry seasons) were tested for MARV antibodies using an indirect ELISA test. The samples were further tested using dot blotting to substantiate the presence of antibodies against MARV glycoprotein (GP). Overall, MARV antibodies were detected in 20.6% of the animals. The species-specific prevalence was 28.7% in cattle, 21.8% in sheep, 19.5% in goats, 15.3% in dogs and 11.2% in pigs. The seropositivity was higher in the rainy season [RR 1.5; 95% CI 1.3–1.8] and in older animals [RR = 2.6; 95% CI 1.9–3.4]. The findings underscore the importance of regular surveillance using the one health approach and future studies into the role of livestock and dogs as potential intermediaries in the circulation of MARV.